Legal highs as an urgent issue of public health - Kapka-Skrzypczak, Lucyna; Cyranka, Małgorzata; Wojtyła, Andrzej (Polish Journal of Public Health, 2011)
Designer drugs, also known as smarts, legal highs, herbal highs and boosters is the term used to describe the group of chemical substances and/or their mixtures which are associated with the production of psychotic symptoms, either real or imaginary. This term cannot be considered scientifically. The intention of designing drugs is to go around existing drug laws by slightly modifying the molecular structure of existing drugs and sell those newly synthesized chemical agents legally. There has been a huge outburst of shops offering designer drugs, so-called head shops or smart shops, in Poland recently. The legal drugs in our country have become an urgent and important social issue, disputed and controversial in terms of drug policy and law, but most of all - because of increasing health hazard, especially for the youth - it is also a matter of public health. This article presents main factors that may influence the anti-drug policy, it concerns also the Internet sale of legal highs and new marketing strategies. It includes recommendations, commentaries and evaluation of latest actions against designer drugs, especially mephedrone, based on British experience in the subject.